Heregulin-1ß and HER3 in hepatocellular carcinoma: status and regulation by insulin. Issue 1 (December 2016) - Buta, Corina; Benabou, Eva; Lequoy, Marie; Régnault, Hélène; Wendum, Dominique; Meratbene, Fatiha; Chettouh, Hamza; Aoudjehane, Lynda; Conti, Filomena; Chrétien, Yves; Scatton, Olivier; Rosmorduc, Olivier; et al.
Abstract Background The heregulin-1ß/HER3-driven pathway is implicated in several epithelial malignancies and its blockade is currently undergoing clinical investigation. Paradoxically, the status and the regulation of this pathway is poorly known in hepatocellular carcinoma (HCC). Methods Using 85 HCC obtained after tumour resection, heregulin-1ß and HER3 expression was evaluated by real-time RT-PCR, ELISA and/or immunohistochemistry. Statistics were performed to analyze associations between gene expression and clinicopathological parameters. The effects of insulin on the heregulin-1ß/HER3 pathway was investigated in four HCC cell lines. Results HER3 mRNA was upregulated in 52 % of tumours, while heregulin-1ß mRNA was downregulated in 82 %. Hepatitis B and C viral infections were respectively associated with high and low HER3 mRNA expression. No association was seen between neither HER3 or heregulin-1ß mRNA and prognostic factors, survival or recurrence. Immunohistochemistry showed predominant cytoplasmic staining of HER3 in tumours but the staining was nonreproducible. HER3 mRNA and protein levels were not correlated in liver tissues. In HCC cells, insulin promoted HER3 proteasomal degradation and inhibited heregulin-1ß stimulation of cell migration. HER3 and insulin receptor co-immunoprecipitated in these cells. The loss of insulin receptor expression by RNA interference sensitized cells to heregulin-1ß-induced AKT phosphorylation. Conclusions Autocrine heregulin-1ß loop is uncommon in HCC and HER3 mRNA expression is differentially influenced by hepatitis viruses. Insulin is a negative regulator of HER3 protein expression and function in HCC cells. Altogether these data may explain why HER3 and heregulin-1ß expression have no prognostic value and suggest that HCC patients are unlikely to derive benefit from HER3-targeted monotherapies.